2021
DOI: 10.1002/nau.24740
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transcutaneous perineal electrostimulation versus intracavitary anal electrostimulation in the treatment of urinary incontinence after a radical prostatectomy: Randomized controlled trial

Abstract: Aim To compare the efficacy of the treatment with transcutaneous perineal electrostimulation versus intracavitary electrostimulation to reduce the frequency of urinary incontinence after radical prostatectomy and the impact on the quality of life (QoL). Methods This single‐blind equivalence‐randomized controlled trial equally (1:1) randomly allocated men with urinary incontinence post radical prostatectomy into surface electrodes perineal group (intervention group, IG) and intra‐anal probe group (control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In most of the analyzed research protocols, electrostimulation was combined with other PFM therapeutic techniques [ 16 , 27 , 30 , 33 , 40 , 48 , 52 ] and lasted between 15 [ 16 , 31 , 40 , 52 ] and 20 min [ 27 , 33 , 34 ]. Ahmed et al [ 16 ] observed that UI therapy outcomes may improve after combining ES therapy with BF [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In most of the analyzed research protocols, electrostimulation was combined with other PFM therapeutic techniques [ 16 , 27 , 30 , 33 , 40 , 48 , 52 ] and lasted between 15 [ 16 , 31 , 40 , 52 ] and 20 min [ 27 , 33 , 34 ]. Ahmed et al [ 16 ] observed that UI therapy outcomes may improve after combining ES therapy with BF [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…ES is most often combined with PFMT in the treatment of UI [ 27 , 30 , 31 , 40 , 48 ]. It has been shown that transcutaneous and anal electrostimulation when combined with PMFT significantly reduces UI symptoms in men after RP [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations